If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 6 + x = -1x + -9y Reorder the terms: 6 + x + 2y = -1x + -9y Solving 6 + x + 2y = -1x + -9y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + x + x + 2y = -1x + x + -9y Combine like terms: x + x = 2x 6 + 2x + 2y = -1x + x + -9y Combine like terms: -1x + x = 0 6 + 2x + 2y = 0 + -9y 6 + 2x + 2y = -9y Add '-6' to each side of the equation. 6 + 2x + -6 + 2y = -6 + -9y Reorder the terms: 6 + -6 + 2x + 2y = -6 + -9y Combine like terms: 6 + -6 = 0 0 + 2x + 2y = -6 + -9y 2x + 2y = -6 + -9y Add '-2y' to each side of the equation. 2x + 2y + -2y = -6 + -9y + -2y Combine like terms: 2y + -2y = 0 2x + 0 = -6 + -9y + -2y 2x = -6 + -9y + -2y Combine like terms: -9y + -2y = -11y 2x = -6 + -11y Divide each side by '2'. x = -3 + -5.5y Simplifying x = -3 + -5.5y
| 1+6x=4x(3-2x) | | 46=6+4x | | f(x)=2x^4+x^3-3x^2-2x | | 8x^2(3-2x)=0 | | 2(x+1)2+3=0 | | y=2x^3-9x^2 | | 4√(1/4)^x1/16 | | x+6y-22=0 | | 18x^2+45=0 | | y=cos(-0.5x) | | 6(3x+4y)=18x+24y | | f(x)=cos(-6x+7) | | .6435x=2338.57 | | 623.54x=401.25 | | 4/7(21/8x+1/2)=-2(1/7-5/28x) | | 94*x=104*(x-5) | | 1637+.3x=x | | 2x+0.3=-2 | | -2*-x=2x | | (11.6+x)*8=120.8 | | -2*-x= | | -3(1+4p)+5p=-6-6p | | sqrt(x^3+12x^2-11x-2)+sqrt(x^2+3x-4)=0 | | 10(2p-51)-25=(2p-51) | | 3x+10=3,5 | | 4x-20=3x+20 | | b(x-2)+b+1=0 | | 6x+x=224 | | 4x-8=-4(2r-3)+4 | | log[5](x+2)-log[5](x)=log[5] | | 1-3(x+7)=2(2x-1)+3 | | 3/7-x/2=3 |